Packaging Perception: Unveiling Consumer Insights for Brand Success - Patel, Mohit; Chauhan, Rahul; Patel, Himalay; Kalariya, Kush; Soni, Parth (Indonesian Journal Publisher, 2024)
Abstract: This study aims to explore the factors influencing consumer perception of product packaging, with a focus on understanding their impact on brand loyalty and differentiation in the competitive marketplace. Through comprehensive analysis, it seeks to identify key elements that drive consumer preferences and purchase decisions. Employing correlation analysis and statistical testing, this research evaluates the significance of various packaging elements such as colour, imagery, shape, and branding position. Data collected from consumer surveys and market research enables a thorough examination of the relationships between these factors and consumer behaviour. The findings indicate that packaging plays a crucial role in shaping brand loyalty and differentiation. Factors like colour, imagery, and brand positioning significantly influence consumer perception and purchasing decisions, highlighting the importance of strategic packaging design in driving brand success. This research offers actionable insights for businesses seeking to optimize their packaging strategies to enhance brand perception, foster consumer loyalty, and gain a competitive edge in the market. By understanding the nuanced preferences of consumers and leveraging effective packaging elements, companies can create compelling brand experiences that resonate with their target audience.